Immersion to impact: does one or three years of rural immersion influence graduate clinical practice intentions and locations? - Harvey, Will; Ali, Zahra; Van Schaik, Lachlan; Develyn, Tamekha; Wright, Julian (Frontiers in Medicine, 2025)
BackgroundAddressing rural healthcare workforce shortages requires evidence-based strategies in medical education. Extended rural immersion programs offer a potential solution, but the optimal duration for fostering long-term regional and rural practice remains unclear.MethodsThis retrospective study evaluates the impact of one-year versus three-year rural immersion experiences at the University of Melbourne’s Rural Clinical School (RCS) on graduate clinical practice locations of the 2016–2023 graduating cohorts. Using logistic regression analysis, we assessed key predictors of regional and rural practice, including rural immersion duration and intent to practice regionally or rurally.ResultsGraduates who completed the three-year rural immersion program were significantly more likely to practice in Modified Monash Model (MMM) 2–7 areas than those with only one year of rural immersion. Intent to practice regionally or rurally and completing a regional/rural internship emerged as strong predictors of regional/rural practice. However, regional/rural intent did not appear to be a strong indicator for students who only completed 1-year of rural immersion. This highlights the importance of the duration of immersion.ConclusionThe study demonstrates the effectiveness of extended rural immersion in increasing regional and rural workforce retention. Findings support further investment in rural medical education, including end-to-end rural training models, which integrates rural exposure across the entire medical education journey. Future research should examine long-term workforce retention and strategies for sustaining rural career pathways.